Use of Analogy in Science Teaching— A Constructivist Approach - Tandon, Tanu (SCHOOL SCIENCE, 2025)
This paper examines the role of analogy in teaching of science. Analogy is finding similarities between different concepts and utilises learner’s previous knowledge to construct new knowledge. Such construction of knowledge using analogy thus supports and follows premises of constructivism. Constructivism asserts that knowledge is actively constructed by learner based on his previous experiences. Science and scientific concepts are abstract in nature and difficult to understand. Analogy can be used effectively to elucidate and facilitate understanding of scientific concepts. In this paper, examples are discussed where DNA translation is taught using analogy.